PTU-010 Role for GPR15 rather than beta 7 integrins in the pathogenesis of autoimmune liver disease. (June 2019) - Graham, Jonathon; Mukherjee, Suj; Yuksel, Muhammed; Liberal, Rodrigo; Mieli-Vergani, Giorgina; Vergani, Diego; Ma, Yun; Hayee, Bu
Abstract : Introduction: G protein-coupled receptor 15 (GPR15) is a chemoattractant receptor that directs homing of lymphocytes to the colon. Furthermore, it has been shown to be a mediator of effector T cell homing during intestinal inflammation. Evidence exists showing infiltration of gut derived α4β7+ and CCR9+ T cells in the hepatic infiltrate of patients with autoimmune liver disease (AILD), in particular primary sclerosing cholangitis (PSC), with expression of their complementary ligands also being identified on the hepatic endothelium. However, the role of GPR15 in hepatic gut T cell homing remains to be defined. Methods: Explanted liver tissue was collected from patients undergoing orthotopic liver transplantation for chronic liver disease (Alcoholic liver disease [ALD] n=3, Non-alcoholic fatty liver disease [NAFLD] n=3, PSC n=4) with healthy control tissue sourced from patients undergoing hepatocellular carcinoma (HCC) resection (n=4). Liver infiltrating lymphocytes (LIL) were isolated using a mechanical homogenisation and centrifugation/filtration technique. Expression of gut homing markers on T cells was quantified using flow cytometry. Results: Expression of GPR15 was significantly increased on CD4+ effector T cells (CD4+ CD127+ CD45RO+) in NAFLD, ALD and PSC patients compared to healthy controls (9.7 ± 0.4, 12.7 ± 0.9 and 20.1 ± 1.8 vs 4.1 ± 1.8, P<0.05), with a significant increase also observed on CD8+ effector T cells (CD8+ CD45RO+) in PSC patients when compared to healthy controls (16.7 ± 2.6 vs 2.3 ± 0.58, P<0.01). There were also trends towards increased expression of gut homing markers CCR9, α4β7 and αEβ7 on effector CD4+ and CD8+ T cells in all chronic liver disease groups compared with healthy control tissue. Conclusions: For some time, evidence pointed towards β7 integrins as the drivers of the hepatic inflammation seen in patients with AILD and associated inflammatory bowel disease as a result of aberrant effector T cells homing from the gut to the liver. These data reveal a somewhat redundant role for β7 integrins, which could be regarded as a non-disease specific feature of advanced disease, and highlight GPR15 as the primary mediator of effector gut T cell homing.